The Values of Natural Disaster Mitigation in Discourse: The True Story of the Acehnese Tsunami Victims - Denni Iskandar; Tengku Silvana Sinar; Iskandar Abdul Samad; Ahmad Nubli Gadeng (Universitas Muhammadiyah Surakarta, 2022)
This article aims to investigate the values of natural disaster mitigation among Acehnese Tsunami Victims. Natural disaster mitigation is an important issue for people who live in disaster-prone country such as Indonesia. Hermeneutical approach was employed in this study to reveal the values of disaster mitigation contained in the book about true story of the survivors of the Earthquake and Tsunami that occurred on December 26, 2004. The results of this research indicate that there are eighteen values of natural disaster mitigation, with details of 9 mitigation values about what to do when a tsunami occurs, 3 mitigation values about what should be avoided, and 6 mitigation values about preventive measures to reduce tsunami risk. Finally, this research reveals that these empirical facts can corroborate the theories and concepts of mitigation of the Earthquake and Tsunami disaster and also as reference to various educational context.